Effect of Moringa oleifera leaf extract on the postharvest quality of tomato fruits during storage - Liamngee, Kator; Terna, Atsor Christopher; Ussuh, Mark William (Journal of Postharvest Technology, 2019)
The effect of Moringa oleifera leaf extract on the shelf life and postharvest condition of tomato fruits during storage was evaluated. Two varieties of tomato fruits: RioGrande and Roma were collected from different markets in Makurdi metropolis, washed and treated with aqueous extracts of Moringa leaves at different concentrations of 0%w/v, 20%w/v and 100%w/v. The tomato fruits were left in storage for a period of 11 days during which different quality parameters associated with tomato fruits were observed and recorded. These included: decay, marketability, weight and shelf life. The fruits treated with 0%w/v Moringa leaf extract concentration (control fruits) produced the highest decay values while fruits treated with 100%w/v concentration produced the lowest decay values on days 5, 7, 9 and 11. Also, the Rio Grande variety had a higher decay value than the Roma variety on days 7 and 9 but the difference between them was not significant. The marketability of the tomato fruits treated with 100%w/v concentration was higher than those treated with 0%w/v concentration. The Roma variety produced higher marketability values than the Rio Grande variety except on day 5. The Roma variety treated with 100%w/v concentration produced the highest fruit weight on days 5, 7, 9 and 11. Comparatively, all the fruits treated with Moringa extracts had a higher shelf life (11 days) than the untreated fruits (control fruits) (7 days). Four fungi namely: Aspergillus niger, Aspergillus flavus, Aspergillus fumigatus and Penicillium griseofulvum were isolated from decaying tomato fruits. Pathogenicity test revealed that Aspergillus niger caused the highest rot and decay in the Rio Grande variety while Aspergillus flavus caused the highest decay in the Roma variety. The results of this research carried out shows that Moringa oleifera extract can be used to extend the shelf life and preserve the quality of tomato fruits in storage.